(untitled) - Silverman, Jay (Boston, 2006)
This handbook is developed around students' real writing needs, offering advice on the writing and research process, as well as specific guidance on punctuation, mechanics, usage and a wide variety of common assignments.
Keywords: English language,Tiếng Anh; Grammar,Handbooks, manuals, etc.,Ngữ pháp,Sổ tay, hướng dẫn sử dụng, vv